Planning of Fast Charging Station for Electric Vehicles Equipped With Renewable Energy Sources and Energy Storage System Considering Economic and Environmental Objectives - Hannaneh Baghaei; Meisam Jaafari; Mohammad Alizadeh (مجله مدل سازی در مهندسی)
The development of electric vehicles in the transportation sector requires the establishment of charging infrastructures such as fast charging stations. Besides, in order to reduce the pollutants caused by fossil fuel power plants, renewable energy sources (RESs) and energy storage systems should be integrated with fast charging stations. In this article, a mixed-integer linear programming model is presented to determine the capacity of RESs and battery energy storage system in a charging station, considering two objective functions including the minimization of economic costs and emissions. The proposed model considers the possibility of using wind and solar resources and four types of battery technology including lead-acid, nickel-cadmium, lithium-ion, and sodium-sulfur. Regarding the two contradictory objectives in the proposed model, the epsilon constraint method has been employed to obtain the Pareto front for optimal solutions. Then, the fuzzy satisfying method has been used to determine the final solution. The results of the proposed model have been examined in four different planning horizons. The results show that with the increase in the importance of the objective function of reducing emissions, the installed capacity of renewable resources increases..